Pengembangan Inovasi Produk â€œKopi Bubukâ€ Meningkatkan Nilai Jual di Madiun Jawa Timur - Henny Rahmasari; Moh Faizin (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2022)
The development of coffee is currently in great demand by various groups. Coffee is so famous and penetrated in recent years. The coffee grounds that have been served in glasses by many people turned out to have a very long stage. Processing coffee beans is quite complicated, but it is equivalent to the enjoyment obtained from a cup of coffee. In developing a business is to use various ways to increase the selling value of the products sold and to get the profits to be achieved. One of the residents in Krajan Hamlet, Candimulyo Village, named Mbah Narti has a small business, namely a ground coffee business. He has been running this ground coffee business for a long time. In this ground coffee business, Mbah Narti only sells ground coffee in ordinary plastic packaging, without a name tag. The purpose of this study is to develop product innovation in the ground coffee business as an effort to increase the selling value of the product by using the Asset Based Community - Driven Development (ABCD) approach, so that with the development of product innovation it can increase the selling value. With this community service activity, business owners and researchers have achieved product innovation on packaging and labels.